PEMBATASAN HAK MENGUASAI NEGARA OLEH MASYARAKAT ADAT DALAM PENGELOLAAN SUMBER DAYA AIR - Diah Pawestri Maharani (Arena Hukum, 2016)
AbstractWater is a basic requirement of all living creatures on earth. One one hand, the available of water in nature which potentially can be exploited by human tend to quality decline. On the other hand, the need of water always increase over time, not only because of the increace of human population, but also because of the intensity of the variation needs of water as a commercial comodities. Hence the imbalance between supply and demand of water raises conflict. This problem do not only occur among communities, or between societies and investors, but also occur between Indigeneous Communities with the State. In this paper the authors would like to highlight about the authority of the State in managing water resources included in determining policies. State authority is rooted in the constitutional mandate of the 1945 Constitution which states: